A social network typology and sexual risk-taking among men who have sex with men in Cape Town and Port Elizabeth, South Africa. Issue 5 (3rd May 2016) - de Voux, Alex; Baral, Stefan D.; Bekker, Linda-Gail; Beyrer, Chris; Phaswana-Mafuya, Nancy; Siegler, Aaron J.; Sullivan, Patrick S.; Winskell, Kate; Stephenson, Rob
Abstract: Despite the high prevalence of HIV among men who have sex with men in South Africa, very little is known about their lived realities, including their social and sexual networks. Given the influence of social network structure on sexual risk behaviours, a better understanding of the social contexts of men who have sex with men is essential for informing the design of HIV programming and messaging. This study explored social network connectivity, an understudied network attribute, examining self-reported connectivity between friends, family and sex partners. Data were collected in Cape Town and Port Elizabeth, South Africa, from 78 men who have sex with men who participated in in-depth interviews that included a social network mapping component. Five social network types emerged from the content analysis of these social network maps based on the level of connectivity between family, friends and sex partners, and ranged from disconnected to densely connected networks. The ways in which participants reported sexual risk-taking differed across the five network types, revealing diversity in social network profiles. HIV programming and messaging for this population can greatly benefit from recognising the diversity in lived realities and social connections between men who have sex with men.